Pengaruh Self Assessment System dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak - Elia Rossa; Engela Ananta; Ian Arbatona; Josua Christian; Kiran Maharani; Lidia Margaretta Purba (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In research or scientific articles, previous or relevant research is very important because it helps strengthen theories and phenomena of relationships or influences between variables. In this article, literature on Contemporary Tax Studies discusses components that influence Taxpayer Compliance, including the Self Assessment System and Tax Socialization. Building a hypothesis of influence between variables is the aim of this paper. The results of this literature research are as follows: 1) Self Assessment System for Taxpayer Compliance; 2) Tax Socialization of Taxpayer Compliance.